Jalan Panjang Tasawuf: Dari Tasawuf Awal Hingga Neo-Sufisme - Achmad Muzammil Alfan Nasrullah (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2021)
Sufism is a view of the world centered on God Almighty, Allah Almighty. Sufism talks about the essence of God Almighty only and not sinking into those who are not Him. Sufism is a view of the nature of a reality which in philosophy is classified as the science of nature or commonly referred to as